Priming the Arabic dative: Evidence for syntactic abstractness and implicit learning - Alzahrani, Alaa (Frontiers in Education, 2022)
Language speakers are more likely to reuse a recently experienced syntactic structure, a phenomenon known as syntactic priming. However, empirical evidence for syntactic priming comes primarily from a small subset of Indo-European languages. Using a comprehension-to-production priming task, this preliminary study examined immediate and cumulative syntactic priming in Arabic, a language with a different typology than studied thus far. Nine native speakers of Arabic were primed to the Arabic double object dative construction. Results from a logistic regression model indicate that there were significant priming effects across all priming phases, with increased productions of the double object dative (a) during the priming task, (b) immediately after, (c) and two weeks later. These findings provide some support for the proposal that syntactic priming arises from an abstract syntactic level as well as the idea that priming is a form of implicit learning.